Intraspecific Competition for Beans and Corn in the Green House of IPB University Bogor, West Java - Taufik Arianto; Firman Ali Rahman; Muhammad Shohibul Ihsan; Hasan Basri; Sulistijorini (Yayasan Tajuk Indonesia, 2024)
This study aims to analyze the intraspecific competition between peanuts (Arachis hypogaea) and corn (Zea mays) in a controlled environment in the Green House IPB University, Bogor, West Java. Intraspecific competition occurs when individuals of the same species compete with each other for limited resources, such as light, water, and soil nutrients. This study was conducted using a factorial experimental design, involving various levels of planting density in each species. The observed parameters include plant growth, biomass, competition index, and crop yield. The results showed that the interaction between peanuts and corn under intraspecific conditions affected the efficiency of resource use as well as the yield of each plant. These findings provide important insights for the management of mixed cropping patterns, especially in sustainable agricultural systems that prioritize land and resource use efficiency.